Student Awareness of Cybersecurity Rights in the Digital Space - Yessika Nur Hidayah; Musaenda Phillippica Nurilhuda (Konsultan Jurnal Ilmiah Indonesia, 2025)
The dense use of digital spaces among Indonesian students poses relevant cybersecurity risks, characterized by low awareness of cybersecurity rights and practices. Studies show that the average cybersecurity awareness score for students is still in the moderate category (79.5%), with practices such as repeated password use being vulnerable to threats. The main objective of this article is to examine the level of student awareness regarding cybersecurity rights, highlight the challenges of implementing digital security, and recommend effective educational strategies and campus policies. This research uses a qualitative method with a literature review approach, identifying and synthesizing findings from accredited national journals through databases such as Google Scholar and Sinta with keywords such as